Women, Migration and the Exchange of Knowledge from the Sixteenth to the Twenty-first Century - Roman, Nicoleta. author. (orcid)0000-0001-9626-6329 Link aut Link
XXV, 500 p. 49 illus., 39 illus. in color.
Keywords: This book examines female migration between Eastern and Western Europe from the sixteenth to the twentieth century. Bringing together contributions from scholars working in diverse disciplines, the book focuses on the social, economic, and cultural exchanges between migrants and the inhabitants of their host countries, arguing that women were central to these interactions due to their commercial, artisanal, and intellectual skills. The chapters shed light on the various roles and professions that women undertook when migrating across Europe, providing case studies of governesses, domestic servants and caregivers, traders and merchants, doctors and scholars, and emphasising how these roles shaped their identities. The authors illustrate how social mobility was engendered by skilled migration and academic mobility, whilst also illuminating the prejudices and challenges that faced women as they attempted to integrate into their new host societies alongside their families. Taking a comparative approach to explore the experiences of migrants across a range of countries in Europe, and over a vast period from the Habsburg, Ottoman, and Russian Empires up until today, this collection provides insights into the long history of migration between Eastern and Western Europe. Nicoleta Roman is a researcher at the ‘Nicolae Iorga’ Institute of History of the Romanian Academy and at New Europe College- Institute for Advanced Study, both in Bucharest, Romania. Her research interests revolve around social and economic history, gender and the history of women and children in (pre)modern Romania and Southeastern Europe. Beatrice Zucca Micheletto is a researcher in the Department of Cultures, Politics and Society at the University of Turin, Italy where she teaches Economic History of Migration. Her research focuses on economic and social history, women and gender history, migration history and labour history of early modern and modern Europe in Italy and France.